MicroRNAs as Molecular Switches in Macrophage Activation - Curtale, Graziella; Rubino, Marcello; Locati, Massimo (Frontiers in Immunology, 2019)
The efficacy of macrophage- mediated inflammatory response relies on the coordinated expression of key factors, which expression is finely regulated at both transcriptional and post-transcriptional level. Several studies have provided compelling evidence that microRNAs play pivotal roles in modulating macrophage activation, polarization, tissue infiltration and resolution of inflammation. In this review, we highlight the essential molecular mechanisms underlying the different phases of inflammation that are targeted by microRNAs to inhibit or accelerate restoration to tissue integrity and homeostasis. We further review the impact of microRNA-dependent regulation of tumor-associated macrophages and the relative implication for tumor biology.